RESEPSI JAMAAH MAJLIS TA’LIM AT-TAQWA TERHADAP HADIS-HADIS MUSHKIL DAN IMPLIKASINYA DALAM KEPEDULIAN KEPADA SESAMA DENGAN PENDEKATAN PSIKOLOGI ORGANISASI - Hartati Hartati (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2020)
This article discusses the reception of At-Taqwa Majlis Taklim to the mushkil  of hadiths and their implications for social care. The mushkil  of hadi>ths are widely used as study material for woman recitation groups, even though the hadiths are usually used as objects of studies by researchers or scholars of hadiths. From the understanding of At-Taqwa Taklim Majlis, the mushkil  hadiths related to the theme of Aqidah initiated the charity and donation programs of this majlis. This article aimed to find out the reception of At-Taqwa Taklim Majlis’ jama’ah to the four themes of mushkil  hadiths, to elaborate the ulama's explanation, and to examine the relationship of mushkil  hadiths with social care. The methods used in this study were field research and library research with an approach of organizational psychology. The results show that the understanding of At-Taqwa Majlis Taklim jama’ah on mushkil  hadiths was formed through organizational psychology with the indicators of leadership, job satisfaction, employees/members’ motivation, organizational change, and group processes in an organization.